Assessing carbonation in one-part fly ash/slag geopolymer mortar: Change in pore characteristics using the state-of-the-art technique neutron tomography. (November 2020) - Vu, Tran Huyen; Gowripalan, Nadarajah; De Silva, Pre; Paradowska, Anna; Garbe, Ulf; Kidd, Paul; Sirivivatnanon, Vute
Abstract: Carbonation has long been recognised as a durability issue attributed to corrosion of steel reinforcement in geopolymer materials. The currently available information, however, is not sufficient to gain a deep understanding of this issue, particularly the facet of the carbonation impact on the pore structure of such materials. This paper, thus, assessed the influence of carbonation on porosity and pore size characteristics of one-part fly ash/slag geopolymer mortar, by using neutron tomography. The cutting-edge thermal neutron tomography used in this study provided the prowess of non-destructive 3D analysis of exploring different regions within geopolymers. The results obtained showed that carbonation in the investigated geopolymer mortars drew their porosity down approximately 30% and shifted pore size regions to smaller pore areas. Other evaluations such as changing pH, carbonation front depth and elemental mapping by scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry (EDS) were also performed in this study, in order to supplement the findings of neutron tomography.